2016
DOI: 10.7816/nesne-04-07-01
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Resolution Styles Scale in Romantic Relationship: The Validity and Reliability Study

Abstract: 3 ÖZBu çalışmanın amacı çiftlerin çatışma çözüm stillerini ölçmek amacıyla geçerli ve güvenilir bir ölçek geliştirmektir. Bu amaçla 2 ayrı çalışma yürütülmüştür. İlk çalışmada, romantik ilişki yaşayan ya da evli kişilerle yarı yapılandırılmış mülakatlar gerçekleştirilmiştir. Hem bu mülakatlardan oluşturulan maddeler, hem de alanda uzman kişiler tarafından ilgili yazın incelenerek eklenen maddelerle geniş bir madde havuzu oluşturulmuştur. Romantik ilişki yaşayan 200 katılımcıyla (Ort.yaş = 23.13, S.yaş = 2.96) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…The Cronbach's alpha coefficients of the scale are 0.77 for positive conflict resolution styles, 0.81 for negative conflict resolution styles, 0.75 for retreat, and 0.80 for subordination. Higher scores indicate more frequent engagement in the behaviors specified by the subscale 33 . In the current study, the internal consistency coefficient of the scale is found to be 0.73.…”
Section: Methodssupporting
confidence: 49%
See 2 more Smart Citations
“…The Cronbach's alpha coefficients of the scale are 0.77 for positive conflict resolution styles, 0.81 for negative conflict resolution styles, 0.75 for retreat, and 0.80 for subordination. Higher scores indicate more frequent engagement in the behaviors specified by the subscale 33 . In the current study, the internal consistency coefficient of the scale is found to be 0.73.…”
Section: Methodssupporting
confidence: 49%
“…Higher scores indicate more frequent engagement in the behaviors specified by the subscale. 33 In the current study, the internal consistency coefficient of the scale is found to be 0.73.…”
Section: The Conflict Resolution Styles Scale In Romantic Relationshi...mentioning
confidence: 49%
See 1 more Smart Citation
“…The Conflict Resolution Styles Scale (CRSS) was developed by Özen (2006) to develop a valid and reliable scale to measure couples' conflict resolution styles. The CRSS examines each partner's conflict resolution style by using four sub-dimension structure; positive conflict resolution, negative conflict resolution, subordination, and retreat (Özen, Salman-Engin, & Sakallı-Uğurlu, 2016). The CRSS consists of 25 items that are answered using a 6-point Likert-type scale.…”
Section: Conflict Resolution Styles Scale (Crss)mentioning
confidence: 99%
“…Since conflict is an important part of both romantic and marital relationships, how spouses deal with this conflict affects the continuity and maintenance of relationships. In addition, the conflict resolution methods affect both the well-being of partners at the individual level and the perceived satisfaction from the relationship or marriage at the dyadic level (Özen, Salman-Engin, & Sakallı-Uğurlu, 2016). The strategies partners use in their romantic relationships are generally divided into four categories: (1) being able to cope with the existing conflict actively and constructively, (2) showing aggressive and destructive behavior, (3) avoiding and withdrawing from conflict, and (4) complying and obeying the wishes of the partner (Özen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%